1981
DOI: 10.1042/bj1930441
|View full text |Cite
|
Sign up to set email alerts
|

On the reactivity of metallothioneins with 5,5′-dithiobis-(2-nitrobenzoic acid)

Abstract: Rat liver and horse kidney metallothioneins react with 5,5'-dithiobis-(2-nitrobenzoic acid) (Nbs2) to release 5-thio-2-nitrobenzoate and metal ions. The reactions are slow and exhibit biphasic kinetics with each process having an empirical rate law of the form:where RSM represents metal-bound thiolate groups.The pseudo-first-order rates are insensitive to pH but are modified in guanidine hydrochloride solution. Rat liver metallothioneins of variable zinc, copper and cadmium composition react similarly and give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 15 publications
2
46
1
Order By: Relevance
“…We have suggested that this free thiol might be more reactive toward disulfides such as GSSG (4). Herein, we have used Ellman's reagent to investigate the redox behavior of MT, a reaction that has been studied earlier in some detail (13,14,34). Under the conditions of our experiments, the kinetic phase affected by ATP corresponds to the faster of the two phases ascribed by others to the reaction of the ␣-domain of MT (35).…”
Section: Discussionmentioning
confidence: 99%
“…We have suggested that this free thiol might be more reactive toward disulfides such as GSSG (4). Herein, we have used Ellman's reagent to investigate the redox behavior of MT, a reaction that has been studied earlier in some detail (13,14,34). Under the conditions of our experiments, the kinetic phase affected by ATP corresponds to the faster of the two phases ascribed by others to the reaction of the ␣-domain of MT (35).…”
Section: Discussionmentioning
confidence: 99%
“…The assay for free sulfhydryl groups used 5,5Ј-dithiobis(2-nitrobenzoic acid) as described in ref. 37.…”
Section: Preparation Of T and T(o) And Assay Of T(o)mentioning
confidence: 99%
“…The initial reaction is characteristic of free thiol reacting with 5,5'-dithiobis-(2-nitrobenzoic acid), according to studies with horse-kidney 01 metallothionein (Li et al, 1979). The second phase is similar to the reaction observed between 5,5'-dithiobis-(2-nitrobenzoic acid) and thiol groups bound to cadmium, zinc, or copper in the horse kidney protein (Li et al, 1979 . In tumours from zinc-deficient animals, not only was the incorporation of thymidine into DNA greatly depressed, but its uptake into the cells was also greatly inhibited.…”
Section: Characterization Of the Cadmium-and Zinc-binding Proteinmentioning
confidence: 58%
“…As is described elsewhere, colour development is time-dependent, and the increase in absorbance at 412 nm must be followed until the reaction is complete in order to obtain valid results (Li et al, 1979).…”
Section: Preparation Ofcellfractionsmentioning
confidence: 99%